Towards a cost-effective feeding of broiler chickens - Idrus, Zulkifli (Faculty of Animal Husbandry, Brawijaya University, 2017)
As feed constitutes more than 70% of the total cost of production, thus any attempt to reduce feed cost may lead to improved production efficiency and profitability. There is an opportunity to utilize locally available agriculture by-products as a source of energy or protein for broiler chickens. Palm kernel cake (PKC) can be a valuable source of energy for broilers but because of its high fibre content and low level of energy the use of PKC in poultry rations is limited. The availability of energy of PKC can be improved through physical and biochemical treatments. The availability of commercial synthetic amino acids has allowed a reduction of crude protein in poultry diets. Supplementing low-crude protein diets with synthetic amino acids has been shown to save cost. Exogenous emulsifiers may improve fat digestibility, reduce the inclusion level of crude palm oil in the diet of broilers and decrease feed cost substantially because oil is expensive. Vitamin and trace mineral premixes can be withdrawn from corn-soy based finisher diets without any adverse effects on growth performance and well-being of broilers. Such practice could substantially reduce production costs. Practical and innovative strategies to reduce feed costs are critical to ensure the sustainability of the poultry industry.